[Memo from Samuel D Chilcote, Jr to members of the Tobacco Institute Executive Committee regarding an oversight hearing on tobacco products] - Chilcote, S.D. (Tufts Archival Research Center, 2007)
Confidential; Missing Attachments; Memo from Samuel D Chilcote, Jr to members of the Tobacco Institute Executive Committee regarding an oversight hearing on tobacco products. Focuses on discussion of whether or not nicotine is addictive. Summarizes media coverage and lists Congress members present. Discusses testimony of Joseph Califano, Jr, president of the Center on Addiction and Substance Abuse.